Lung colonization by Aspergillus fumigatus is controlled by ZNF77 - Sara Gago (Nature Portfolio, 2018)
Aspergillus fumigatus regularly colonises the lungs but in the context of respiratory disease can be associated with increased pathology. Here the authors show mutations in ZNF77 result in altered bronchial epithelial characteristics and enhanced fungal burden.